PEMANFAATAN TEPUNG CANGKANG TELUR DALAM PEMBUATAN FLAKES [THE UTILIZATION OF EGGSHELL FLOUR IN THE MAKING OF FLAKES] - Lucia Crysanthy Soedirga; Melanie Cornelia (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2021)
Eggshell is one of the major wastes in Indonesia due to the high consumption of chicken and duck eggs. Eggshells contain high level of calcium; thus, they have the potential to be utilize. Flakes are one of the cereal-based products that are widely used for breakfast. The result has shown that duck eggshell flour was the chosen flour with calcium of 4001.42 mg/100g, magnesium of 67.56 mg/100g, and phosphorus of 1250.55 mg/g compared to chicken eggshells. In this study, wheat flour was be substituted with duck eggshell flour at various ratios (1:0, 1:1, 1:2, and 2:1). The scoring results for color, aroma, taste, and texture were 4.79±0.06, 1.99±0.71, 2.06±0.92 and 5.03±0.59, respectively. Moreover, the degree of acceptance wasneutral to slightly like toward color, aroma, taste, texture, and overall acceptance of flakes. Based on organoleptic test, ratio 1:1 was selected as the best ratio for making flakes with a hardness value of 8933.85±357.74, oHue and lightness 89,09o dan 85,87. The best formulation of flakes had calcium of 253.93 mg/100 g, magnesium of 36.91 mg/100 g, and phosphorus of 138.35 mg/100 g, moisture of 3.61±0.05%, ash of 31.76±0.58% of, protein of 10.81±0.06%, fat of 1.70±0.09%, and carbohydrate (by difference) of 52,12%.BAHASA INDONESIA ABSTRAK:Cangkang telur merupakan salah satu limbah yang cukup besar di Indonesia karena tingginya konsumsi telur ayam dan telur bebek. Cangkang telur memiliki kandungan kalsium yang tinggi sehingga berpotensi untuk dimanfaatkan. Flakes adalah salah satu produk berbasis serealia yangbanyak dimanfaatkan untuk sarapan pagi. Hasil penelitian menunjukkan bahwa tepung cangkang telur bebek merupakan tepung terpilih dengan kadar kalsium (4001,42 mg/100g), magnesium (67,56 mg/100g), dan fosfor (1250,55 mg/g). Selain itu, pada penelitian ini, tepung terigu akan disubsitusi dengan tepung cangkang telur bebek pada berbagai rasio (1:0, 1:1, 1:2, dan 2:1).Hasil skoring warna (4,79±0,06), aroma (1,99±0,71), rasa (2,06±0,92), tekstur (5,03±0,59). Selain itu, tingkat kesukaan panelis terhadap flakes adalah netral hingga agak suka untuk atribut warna, aroma, rasa, tekstur, dan penerimaan keseluruhan. Berdasarkan uji organoleptik ini, rasio 1:1 antara tepung terigu dan tepung cangkang telur bebek merupakan rasio terpilih padapembuatan flakes. Flakes terbaik ini memiliki nilai kekerasan sebesar 8933,85±357,74, oHue dan lightness 89,09o dan 85,87. Flakes pada formulasi terpilih memiliki kadar kalsium (253.93 mg/100 g), magnesium (36.91 mg/100 g), dan fosfor (138.35 mg/100 g), kadar air (3,61±0,05%), kadar abu; (31,76±0,58%), kadar protein (10,81±0,06%), kadar lemak (1,70±0,09%) kadar karbohidrat (by difference) (52,12%).